Coprophagia in an 8-Year-Old Hospitalized Patient: A Case Report and Review of the Literature. (27th November 2017) - Bacewicz, Aleksandra; Martin, Katherine
Abstract : Consult-liaison psychiatrists often encounter difficult clinical scenarios. We present a pediatric case of presumptive coprophagia. After a negative medical work-up, the pediatrics team asked psychiatry to assist them in managing this relatively rare disorder in the hospital setting. Little is known about the etiology and treatment of coprophagia in the pediatric population. Using the case as a catalyst, we discuss what is known about this disorder as well as treatment strategies in the hospital setting.